A comparative analysis of flow boiling in micro-gaps with internal micro-fins of rectangular and triangular profiles - Ahmed, Shugata; Ismail, Ahmad Faris; Sulaeman, Erwin; Hasan, Muhammad Hasibul (Research India Publications, 2016)
Micro-gap heat sinks can be used for extensive evaporative cooling of micro-electronic devices, micro-electro-mechanical systems (MEMS) and micro-opto-elecro-mechanical systems (MOEMS). Internal micro-fins may increase two-phase heat transfer rate by extending surface area. However, excessive pressure drop is one of the significant drawbacks of two-phase cooling. Fin shapes play an imperative role in flow boiling heat transfer rate and pressure drop penalty. The scope of this paper is to estimate two-phase heat and mass transfer, pressure drop, wall shear stress development and turbulent characteristics of micro-gaps with rectangular and triangular micro-fins by numerical simulation using water coolant. Simulation has been carried out by FLUENT 14.5 release. Volume of fluid (VOF) model along with Renormalization Group Theory (RNG) k-ɛ turbulence model has been used for fluid flow and heat transfer modeling. Governing equations have been solved numerically by Finite Volume Method (FVM). Simulation results demonstrate that thermal resistance of triangular fin micro-gap is higher than rectangular fin heat sink. Thermal resistance declines with pumping power increment. However, for both of the heat sinks, decrement rate drops-off after 0.004 W pumping power. In comparison to triangular fin micro-gap, turbulent kinetic energy generation is found higher for rectangular fin heat sink. Although rectangular fin micro-gap shows superior heat transfer performance, pressure drop penalty is also larger than triangular fin micro-gap. Hence, it is recommended that pressure drop should be minimized by optimizing geometrical parameters and boundary conditions.